Architecture of gene regulatory networks controlling flower development in Arabidopsis thaliana. Issue 1 (December 2018) - Chen, Dijun; Yan, Wenhao; Fu, Liang-Yu; Kaufmann, Kerstin
Abstract Floral homeotic transcription factors (TFs) act in a combinatorial manner to specify the organ identities in the flower. However, the architecture and the function of the gene regulatory network (GRN) controlling floral organ specification is still poorly understood. In particular, the interconnections of homeotic TFs, microRNAs (miRNAs) and other factors controlling organ initiation and growth have not been studied systematically so far. Here, using a combination of genome-wide TF binding, mRNA and miRNA expression data, we reconstruct the dynamic GRN controlling floral meristem development and organ differentiation. We identify prevalent feed-forward loops (FFLs) mediated by floral homeotic TFs and miRNAs that regulate common targets. Experimental validation of a coherent FFL shows that petal size is controlled by the SEPALLATA3-regulated miR319/TCP4 module. We further show that combinatorial DNA-binding of homeotic factors and selected other TFs is predictive of organ-specific patterns of gene expression. Our results provide a valuable resource for studying molecular regulatory processes underlying floral organ specification in plants. Homeotic transcription factors and miRNAs promote floral organ specification. Here Chen et al. reconstruct gene regulatory networks inArabidopsis flowers and find evidence for feed forward loops between transcription factors, miRNAs and their targets that determine organ-specific gene expression.